An assessment of innovation profiles of telecom operators: a longitudinal comparison between BT and Orange from 2004 to 2013 - Pierre Vialle; Samuel Beltran; Jason Whalley (International Telecommunications Society (ITS), 2015)
A large body of research has focused on measuring innovation and the innovativeness of firms. One option frequently chosen is to analyse quantitative indicators published, often at the expense of an intimate understanding of the specific industry or firm context. Another option is to rely on in-depth case analysis relying on methods such as extensive interviews, which can be difficult to implement for various reasons. Little research specifically focuses on network operators, and in particular over a long period In this paper we explore a methodology based on publicly available information for assessing and characterising the innovation profile of telecom operators over time. It combines quantitative and qualitative analysis and relies on an understanding of telecom operators' business. This methodology aims at allowing comparison between operators, and also to enable linking the observed innovation patterns. For example the innovation patterns observed can be related to external events such as changes in market, competition, regulation or technology. They can also be related to internal events such as change in top management or financial events. So far we have included three components in this approach: (1) an analysis of quantitative indicators, (2) an analysis of service releases, and (3) an analysis of statements of Chairmen and CEOs. The main source is annual reports of companies. In this paper, we present an exploratory analysis of two operators, BT and FT/Orange from 2004 to 2013.
Keywords: 330; Innovativeness; innovation; telecommunications; BT; France Télécom / Orange